Investigation of Cytotoxicity, Oxidative Stress, and Inflammatory Responses of Tantalum Nanoparticles in THP-1-Derived Macrophages - Li Zhang; El-Mustapha Haddouti; Hannes Beckert; Ralf Biehl; Shyam Pariyar; Julian M. Rüwald; Xian Li; Max Jaenisch; Christof Burger; Dieter C. Wirtz; Koroush Kabir; Frank A. Schildberg (Hindawi Limited, 2020)
Tantalum (Ta) is gaining attention as a biomaterial in bone tissue engineering. Although the clinical advantage of Ta-based implants for primary and revision total joint replacement (TJA) has been well documented, few studies investigated the effect of wear products of Ta implants on peri-implant cells, and their potential contribution to aseptic implant loosening. This study is aimed at examining the cytotoxicity, oxidative stress, and proinflammatory potential of Ta and TiO2 nanoparticles (NPs) on macrophages in vitro. NPs were characterized using scanning electron microscopy, dynamic light scattering, and energy-dispersive X-ray. To test the NP-mediated cellular response in macrophages, THP-1-derived macrophages were challenged with both NPs, and cytotoxicity was analyzed using CCK-8 and LDH assays. Flow cytometry was used to investigate particle uptake and their internalization routes. NP-mediated oxidative stress was investigated by measuring the production of reactive oxygen species, and their proinflammatory potential was determined by quantifying the production of TNFα and IL-1β in cell culture supernatants using ELISA. We found that both Ta and TiO2 NPs were taken up through actin-dependent phagocytosis, although TiO2 NPs did also show some involvement of macropinocytosis and clathrin-mediated endocytosis. Ta NPs caused no apparent toxicity, while TiO2 NPs demonstrated significant cytotoxicity at a concentration of over 100μg/mL at 24 h. Ta NPs induced negligible ROS generation and proinflammatory cytokines (TNFα, IL-1β) in macrophages. In contrast, TiO2 NPs markedly induced these effects in a dose-dependent manner. Our findings indicate that Ta NPs are inert, nontoxic, and noninflammatory. Therefore, Ta could be considered an excellent biomaterial in primary and revision joint arthroplasty implants.